2023
DOI: 10.1021/acs.jpcc.2c08308
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Photoluminescence and Stability of Mn-Doped Cs2InCl5·H2O Microcrystals with Introduced Bi3+ Ion

Abstract: In this work, lead-free zero-dimensional (0D) all-inorganic perovskite Mn 2+ -doped Cs 2 InCl 5 •H 2 O microcrystals (MCs) with introduced Bi 3+ ion were synthesized by supersaturation recrystallization at room temperature. The electronic bandgap of the MCs is tuned from ∼5.1 to ∼3.1 eV, and the electronic absorption is enhanced in the 200−400 nm region by Bi 3+ incorporation. Upon excitation at 365 nm, the MCs with introduced Bi 3+ exhibit strong red emission peaking at 640 nm, which is attributed to the Mn 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…The hyperfine splitting energy is ∼9.6 mT (96 G), which indicates the presence of Mn 2+ ions in the octahedral coordination environment. The result provides direct experimental access to the alignment ordering of the Mn 2+ spins and to the presence of magnetic coupling effects that are indicative of inter dopant interactions, confirming that Mn 2+ ions are successfully doped to the lattice site of Cd 2+ ions . By Fourier transform infrared (FTIR) spectra (Figure S1), both B-EACC and B-EACC:20%Mn 2+ are retained unchanged, confirmed by the appearance of the stretching vibration of ether bonds at around 1110 cm –1 .…”
Section: Resultsmentioning
confidence: 61%
“…The hyperfine splitting energy is ∼9.6 mT (96 G), which indicates the presence of Mn 2+ ions in the octahedral coordination environment. The result provides direct experimental access to the alignment ordering of the Mn 2+ spins and to the presence of magnetic coupling effects that are indicative of inter dopant interactions, confirming that Mn 2+ ions are successfully doped to the lattice site of Cd 2+ ions . By Fourier transform infrared (FTIR) spectra (Figure S1), both B-EACC and B-EACC:20%Mn 2+ are retained unchanged, confirmed by the appearance of the stretching vibration of ether bonds at around 1110 cm –1 .…”
Section: Resultsmentioning
confidence: 61%
“…On further increase in the Mn 2+ content, the photoluminescence efficiency dropped as a concentration-dependent quenching started to take effect. , The highest PLQY value measured was 57.2%, which was much higher than the highest PLQY of 4.6% of Cs 4 Cd 1– x Mn x Bi 2 Cl 12 layered double perovskite nanocrystals reported by Chen et al and slightly higher than the highest PLQY of 56.6% of Cs 4 Cd 1– x Mn x Bi 2 Cl 12 layered double perovskite crystallites reported by Woodward et al We measured the fluorescence lifetime to assess the fluorescence attenuation of Cs 4 Cd 0.7 Mn 0.3 Bi 2 Cl 12 . As shown in Figure d, the lifetime is 487.36 μs, which is much higher than the previously reported lifetimes of Cs 4 MnBi 2 Cl 12 , indicating that at a high content of Cd 2+ , the nonradiative pathway of Mn 2+ was inhibited, and the luminous efficiency was improved. ,, Next, the full and fine XPS characterization of Cs 4 Cd 1– x Mn x Bi 2 Cl 12 showed typical signal peaks of Cs 3d, Cd 3d, Mn 2p, Bi 4f, and Cl 2p (Figures e and S6); the high-resolution XPS spectrum of Mn verifies the existence of Mn 2p, and its binding energy at approximately 640.2 and 651.7 eV corresponds to 2p 3/2 and 2p 1/2 of Mn 2+ , respectively, confirming the presence of divalent manganese (Figure f), which is consistent with previous reports. , These results showed that CsCdCl 3 , after Mn 2+ doping, was able to participate in the synthesis of two-dimensional layered double perovskite Cs 4 Cd 1– x Mn x Bi 2 Cl 12 with Cs 3 Bi 2 Cl 9 and realize the tuning of Mn 2+ luminescence properties from CsCd 1– x Mn x Cl 3 to Cs 4 Cd 1– x Mn x Bi 2 Cl 12 .…”
Section: Resultsmentioning
confidence: 66%
“…As shown in Figure 4d, the lifetime is 487.36 μs, which is much higher than the previously reported lifetimes of Cs 4 MnBi 2 Cl 12 , indicating that at a high content of Cd 2+ , the nonradiative pathway of Mn 2+ was inhibited, and the luminous efficiency was improved. 21,22,26 Next, the full and fine XPS characterization of Cs 4 Cd 1−x Mn x Bi 2 Cl 12 showed typical signal peaks of Cs 3d, Cd 3d, Mn 2p, Bi 4f, and Cl 2p (Figures 4e and S6); the high-resolution XPS spectrum of Mn verifies the existence of Mn 2p, and its binding energy at approximately 640.2 and 651.7 eV corresponds to 2p 3/2 and 2p 1/2 of Mn 2+ , respectively, confirming the presence of divalent manganese (Figure 4f), which is consistent with previous reports. 23,26 These results showed that CsCdCl 3 , after Mn 2+ doping, was able to participate in the synthesis of twodimensional layered double perovskite Cs 4 Cd 1−x Mn x Bi 2 Cl 12 with Cs 3 Bi 2 Cl 9 and realize the tuning of Mn 2+ luminescence properties from CsCd 1−x Mn x Cl 3 to Cs 4 Cd 1−x Mn x Bi 2 Cl 12 .…”
Section: Resultsmentioning
confidence: 99%
“…S5, ESI †), and which is consistent with previous reports. 36,37 Morphological characterization of the three samples using SEM showed blocks with irregular morphology and of micrometer sizes. The EDS mapping showed evenly distributed elements, and that the content of each element was consistent with the actual amount used in the synthesis (Fig.…”
Section: Resultsmentioning
confidence: 98%